Papel da hidrofobicidade na evolução de proteínas - Pimentel, Laís Ozelin de Lima [UNESP] (2015)
Proteins are the most abundant molecules in the cell, being of crucial importance for your functioning, performing regulatory functions both as structural. A protein becomes biologically active passing through a process called folding and then achieves your native state. Among several factors that influence the protein folding, one that has a great participation is the protein hydrophobicity, which occurs because of physical properties of side chains of amino acids. The hydrophobicity contributes to form a compact and stable core, also participates of contacts formation. In previous work (J. Chem. Phys. 125, 084904, 2006), was showed that inserting a mutation in a protein can cause different effects depending on its global hydrophobicity. Proteins with low hydrophobicity showed sensibility to mutations, resulting in a slower folding rate, while proteins with high hydrophobicity remain almost the same. This work will present the influence of global hydrophobicity in sequence variability throughout evolution. This work aims to show the influence of mean hydrophobicity in protein sequence variability and subsequently correlate with Φ values and direct coupling between aminoacids forming a contact.